O sentimento de pertença nas crianças da educação infantil em relação à água nos espaços educativos - Morhy, Priscila Eduarda Dessimoni (2018)
The research approaches the theme water as an element to bring out the feeling of belonging in the small children of children's education using environmental education as the focus. Working with the theme of water is fundamental since it is a natural resource that has a direct impact on the quality and well-being of the environment and life on Earth. Promoting environmental education in children's education is extremely relevant to the maintenance of environmental balance on the planet. In the Amazon there are numerous educational spaces that make it possible to work and develop a relationship and reconnection with water. The objective of the research is to understand how in children the emergence of the feeling of belonging of the water in the perspective of values about the environment. The research is of the qualitative type, participant with descriptive character. It was developed in the CMEI Professora Maria de Fátima Marques Campos, with 50 children and two teachers. With this work it was possible: to know the pedagogical practices used by the teacher in relation to the environmental themes; indicate a pedagogical path for the emergence of young children's feeling of belonging to water; and, to construct categories to systematize the indicator of the feeling of belonging to record changes in habits and attitudes of children in relation to the element of water and the environment as a whole